Pressure Ulcer Prevention: Examine Best Practices for Managing Pressure Ulcers in Immobile Patients and Evaluate the Efficacy of Prevention Strategies - Noreen, Atika; Fatima, Noreen; Arshed, Aqsa; Ali, Faisal; Attiq-Ur-Rehman; Elahi, Ahsan; Khan, Naeem Ullah (Indus Journal of Bioscience Research, 2025)
Pressure ulcers, also known as bedsores or decubitus ulcers, are localized injuries to the skin and underlying tissue, primarily caused by prolonged pressure, shear, or friction. Immobile patients, especially those confined to bed or wheelchair-bound, are at a heightened risk. he management of pressure ulcers requires an interdisciplinary approach, incorporating clinical assessment, patient-specific risk evaluation, use of support surfaces, optimal nutrition, skin care regimens, and scheduled repositioning. Evidence-based tools such as the Braden Scale, Norton Scale, and Waterlow Score have demonstrated efficacy in identifying patients at risk, thereby enabling early intervention. Repositioning protocols—typically recommended every two hours—remain a cornerstone of preventive care. Specialized pressure-relieving devices, including low-air-loss mattresses, gel cushions, and heel protectors, have also shown to significantly reduce the incidence of pressure injuries by minimizing mechanical forces on vulnerable areas.Skin integrity maintenance, through the use of barrier creams, gentle cleansing agents, and moisture-wicking materials, further supports the prevention process, especially in patients with incontinence or compromised skin health. Nutritional support is equally crucial; adequate protein, caloric intake, and essential micronutrients enhance skin repair and immune function, reducing susceptibility to breakdown. This abstract also evaluates recent technological advancements and innovations such as wearable pressure sensors and smart beds, which provide real-time feedback and automated repositioning alerts. These innovations have been associated with improved compliance and outcomes in various clinical settings.In conclusion, the prevention and management of pressure ulcers in immobile patients rely heavily on early risk identification, consistent implementation of preventative protocols, and the integration of technological and clinical best practices. While current strategies are largely effective, continuous education, individualized care plans, and the adoption of emerging technologies will be essential in further reducing pressure ulcer prevalence and improving patient outcomes. This research paper explores the best practices for managing and preventing pressure ulcers in immobile patients and evaluates the efficacy of various prevention strategies. A combination of literature review and collected data from healthcare facilities has been used to assess outcomes.